Chromium-containing small pore mesoporous silicas: synthesis, characterization and catalytic behavior in the liquid phase oxidation of cyclohexane - Shylesh, S.; Samuel, Prinson P.; Singh, A. P. (Applied Catalysis A-General, 2007)
Organic-inorganic hybrid mesoporous silica materials containing chromium and various organo trialkoxysilanes (chloropropyl, vinyl, methyl) were prepared by the co-condensation method, in the presence of cetyl trimethyl ammonium surfactants. The hybrid material, containing chromium, retains one X-ray diffractogram (XRD) peak up to a molar ratio of 1: 1 between tetra ethyl orthosilicate (TEOS) and organosilane in the synthesis gel. Small pore mesoporous chromium-silica samples can be prepared from the large pore hybrid mesoporous chromium samples by calcination. By this method, the pore size of the material can be tailored into the supermicroporous region, without changing the chain length of the surfactant used in the assembly process, as judged from the XRD and N-2 sorption isotherms. The shrinkage in pore size is dependent on the nature and percentage of the organic pendant groups, such that the chloro propyl and vinyl pendant mesoporous material show more pore size shrinkage than the smaller methyl pendant units. Because of the tailorable pore size and with better textural characteristics, the chromium samples show better catalytic activity in the aerial oxidation reaction of cyclohexane than the conventional chromium-containing mesoporous material, like Cr-MCM-41, under a solvent free system. Among the porous chromium catalysts, the samples prepared using chloro propyl silane show higher cyclohexane conversion and cyclohexanone selectivity and behave as a true heterogeneous catalyst. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: chromium; Cyclohexane; Oxidation; small pore silicas

Ethane bridged hybrid mesoporous silsesquioxanes with sulfonic acid functionalities: synthesis, characterization and catalytic applications - Shylesh, S.; Samuel, Prinson P.; Parischa, Renu; Singh, A. P. (From Zeolites to Porous Mof Materials: the 40th Anniversary of International Zeolite Conference, Proceedings of the 15th International Zeolite Conference, 2007)
Periodic mesoporous organosilicas having -CH(2)-CH(2)- groups in the framewall positions and sulfonic acid groups in the pore channels were prepared using 1,2-bis(triethoxysilyl) ethane, 3-mercaptopropyltriethoxysilane and cetyltrimethylammonium surfactant, under basic conditions, by a one-pot synthesis method. XRD, N(2) sorption isotherm and TEM analysis revealed that the mesoporous structural ordering is retained after the functionalization of organic groups while solid-state NMR techniques like (13)C CP MAS NMR and (29)Si MAS NMR show the presence of sulfonic acid groups and the stability of the mesoporous framework with integrated ethane moieties as bridging groups. The hybrid material was more active, selective and stable than the conventional sulfonic acid containing mesoporous catalysts in the Claisen-Schmidt condensation of acetophenone with benzaldehyde to form chalcone.

Sulfonic acid functionalized mesoporous silicas and organosilicas: synthesis, characterization and catalytic applications - Shylesh, S.; Samuel, Prinson P.; Srilakshmi, Ch.; Parischa, Renu; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2007)
Ethane bridged mesoporous organosilicas and MCM-41 having sulfonic acid groups in the pore channels were prepared by co-condensation method as well as grafting method, using 3-mercaptopropyltriethoxysilane (3-MPTS) as the sulfur precursor. TEM and N-2 sorption isotherm analysis revealed that the mesoporous structural ordering is retained after the functionalization and modifications of organic groups while FT-IR, Raman, XPS and solid-state C-13 CP MAS NMR shows the presence of sulfonic acid groups and the stability of the mesoporous framework. The catalytic activity of the developed materials was evaluated in the liquid phase Claisen-Schmidt condensation reaction of acetophenone with benzaldehyde, to probe the effect of mesoporous support surfaces as well as the role of preparation methods. Results showed that sulfonic acid functionalized ethane-silica samples were more active, selective and stable than the conventional sulfonic acid containing mesoporous catalysts. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: condensation; ethane-silica; heterogeneity; sulfonic acids

Synthesis of hydrothermally stable aluminium-containing ethane-silica hybrid mesoporous materials using different aluminium sources - Shylesh, S.; Samuel, Prinson P.; Singh, A. P. (Microporous and Mesoporous Materials, 2007)
Aluminium-containing ethane-silica hybrid mesoporous materials having ethane groups in the frame wall positions are synthesized using aluminium isopropoxide as well as aluminium nitrate as the aluminium sources. The materials were characterized in detail using powder XRD, N-2 adsorption-desorption, SEM, TEM, TG-DTG, TPD, Si-29, C-13 and Al-27 MAS NMR techniques. Characterization techniques revealed that aluminium isopropoxide was the appropriate source for the synthesis of organo aluminosilicas on considering the structural ordering, acidity as well as the percentage of aluminium incorporation into the ethane bridge. Al-27 MAS NMR displays aluminium as tetrahedrally coordinated in both the aluminium-containing organosilicas. Unlike the conventional EtOH-HCl template extraction process, in the present studies, we had used EtOH-NH4OH as the surfactant-extracting medium and chemical analysis results suggest that using this procedure the extent of dealumination can be greatly reduced. XRD and nitrogen physisorption studies further proved that the materials are hydrothermally stable, that the ordered pore channels retains its structure even after 150 h reflux in boiling water, while the conventional Al-MCM-41 catalyst collapsed its mesostructure after 50 h reflux in water. The improved hydrothermal stability of the hybrid materials, even in presence of sodium ions, is attributed to the thick pore walls as well as due to the presence of hydrophobic bridging ethane groups in the wall positions. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: Al-HMM; Al-MCM-4l; hybrid materials; Hydrothermal stability

Periodic mesoporous silicas and organosilicas: an overview towards catalysis - Shylesh, S.; Samuel, Prinson P.; Sisodiya, Sheetal; Singh, A. P. (Catalysis Surveys from Asia, 2008)
Micelle-templated mesoporous and organic-inorganic hybrid mesoporous materials are important in many fields of material research, especially for hosting catalysts in confined space. Among this class, the recent discovery of periodic mesoporous organosilicas (PMOs) represent an exciting new group of organic-inorganic nanocomposites targeted for a broad range of applications ranging from catalysis to microelectronics. Compared to the earlier generation of organic-inorganic hybrid mesoporous samples, obtained by the cocondensation reaction or by the grafting reaction, PMOs represent the right combination of organic and inorganic groups in the frame wall positions. This article reviews the current state of art in organic-inorganic hybrid mesoporous material research with special emphasis over periodic mesoporous organosilica materials having various redox centers (Ti, V, Cr) suitable for oxidation reactions as well as acidic sites (Al, -SO(3)H) for the organic transformation of bulky molecules.
Keywords: Acid catalysis; epoxidation; Mesoporous organosilicas; Organic-inorganic hybrid materials